2009
DOI: 10.1080/87565640802646759
|View full text |Cite
|
Sign up to set email alerts
|

Main and Interaction Effects of Iron, Zinc, Lead, and Parenting on Children's Cognitive Outcomes

Abstract: This study examined relations of blood lead < 10 microg/dL, iron, zinc, and parenting to Head Start children's (N = 112) scores on Peabody Picture Vocabulary Test-III (PPVT-III) and McCarthy Scales of Children's Abilities (MSCA). Venous whole blood and plasma samples were analyzed for lead and zinc by ICP-MS and iron status was assessed by serum transferrin receptors. Hierarchical regressions revealed significant effects of lead on MSCA perceptual scores and iron on PPVT-III and MSCA verbal scores. Children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Plasma levels of copper ( 63 Cu & 65 Cu), iron ( 54 Fe & 57 Fe), manganese ( 55 Mn), selenium ( 82 Se), and zinc ( 66 Zn) were measured using inductively coupled plasma quadrupole mass spectroscopy (Elan 9000; Perkin Elmer, Norwalk, CT) as described. 30 All plasma samples were diluted 20-fold (200 μL diluted to 4 mL) with 0.1% nitric oxide (GFS Chemicals, Powell, OH) in ultra-pure water. Standard solutions of selected trace elements were prepared by dilution of certified standard solutions (Perkin Elmer, Norwalk, CT).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma levels of copper ( 63 Cu & 65 Cu), iron ( 54 Fe & 57 Fe), manganese ( 55 Mn), selenium ( 82 Se), and zinc ( 66 Zn) were measured using inductively coupled plasma quadrupole mass spectroscopy (Elan 9000; Perkin Elmer, Norwalk, CT) as described. 30 All plasma samples were diluted 20-fold (200 μL diluted to 4 mL) with 0.1% nitric oxide (GFS Chemicals, Powell, OH) in ultra-pure water. Standard solutions of selected trace elements were prepared by dilution of certified standard solutions (Perkin Elmer, Norwalk, CT).…”
Section: Methodsmentioning
confidence: 99%
“…Of these three studies, two tested mediation models evaluating if effects of SES were mediated by lead exposures [29,30] and one considered lead as modifying the influence of the psychosocial exposure (maternal self-esteem) [37]. In terms of the environmental exposures, eight examined metals [29,30,34,35,[37][38][39][40], one considered organophosphate exposures [31], two examined PCBs and/or dioxin exposure [36,41], one considered tobacco smoke [32], one examined traffic-related black carbon [28], and one considered airborne polycyclic aromatic hydrocarbons [33•]. For the social factors, five considered a range of psychosocial factors and stressors (e.g., negative life events, maternal distress, parenting behaviors, cognitive stimulation in the home) [28, 31, 33•, 36, 40], five focused solely on SES [29,30,32,39,41], one examined both SES and psychosocial factors as separate modifiers [35,38], and two studies considered maternal self-esteem [34,37].…”
Section: Cognitive and Behavioral Outcomesmentioning
confidence: 99%
“…For the social factors, five considered a range of psychosocial factors and stressors (e.g., negative life events, maternal distress, parenting behaviors, cognitive stimulation in the home) [28, 31, 33•, 36, 40], five focused solely on SES [29,30,32,39,41], one examined both SES and psychosocial factors as separate modifiers [35,38], and two studies considered maternal self-esteem [34,37]. Twelve studies tested effect modification hypotheses, and of those that did so, ten (83 %) observed synergistic associations between environmental and social/psychosocial exposures for child cognitive and behavioral risk [28,[32][33][34][35][36][37][38][39][40]. Two other studies found lead exposure to mediate the association between early-life SES and biomarker-assessed stress reactivity in childhood [29,30].…”
Section: Cognitive and Behavioral Outcomesmentioning
confidence: 99%
See 2 more Smart Citations